Perancangan Kawasan Permukiman Tepi Sungai dengan Konsep Eco-Green Living di Kelurahan Peterongan, Semarang Selatan - Diah Intan Kusumo Dewi (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
The area directly adjacent to the waters is called the waterfront area. Waterfront area has many dvantages compared to other areas. Semarang city is one of the cities that have many spaces of the city whose growth starts from the development of the river corridor area, Semarang City should be able to take advantage of the potential becomes a distinct advantage. The principle of waterfront design is the basics of the arrangement of the city or region that includes various aspects of considerations and components of arrangement to achieve a good urban design. Micro area is one of the areas traversed by the East Canal River flood of Manggis River and included into the sub-district of Peterongan with an area of 10.5 hectares. The function of the micro area is as a residential and trade & services area. However, trading activities that located in designated areas dominated by street vendors who trade on the banks of rivers tend to be wild and unorganized, while the residential areas on the banks of the river can be said to be slum area. Therefore, by using the concept of